External-Ligand-Free, Nickel-Catalyzed Alkenylation of N-Sulfonylamines with Internal Alkynes - Li, Jia-Yue; Li, Lun; Lin, Yun-Zhi; Shi, Hang (Synthesis, 2022)
Allylic amines were synthesized via a nickel-catalyzed coupling reaction between various N-sulfonylamines and internal alkynes. The catalytic reaction was by-product-free and proceeded without the need for additional oxidant/reductant or activating reagent. As improvements over established methods, the present approach avoids the need for an external ligand, which increases the value of the approach with respect to atom economy, and it uses bench-stable Ni(II)Br2(dme) instead of Ni(0)(COD)2 as the source of the nickel catalyst. Mechanistic studies revealed that a catalytic amount of a strong base (i.e., KOtBu) was essential for the formation of active Ni(0) catalyst, which, along with an imine intermediate, then initiated the catalytic cycle.
Keywords: nickel; ligand-free; N-sulfonylallylic amine; alkenylation; cyclometallation